The Dynamics of The CMA Spores Population In Mass Propagation of Two Greenhouses - Widiastuti, Happy; Salsa Bilah Alzahra (Journal of Tropical Mycorrhiza, 2025)
The production of arbuscular mycorrhizal fungi (AMF) propagules is highly necessary for AMF-based biofertilizer production. This research was conducted to ustudy the dynamics of spore populations in mass propagation of AMF propagules in two greenhouses. AMF propagule propagation was carried out in vitro using sorghum plants as host plants grown in 5 kg capacity polybags totaling 200 polybags in all. The results showed that the reactions of both greenhouse H and greenhouse I media was acidic. There was a dynamics of AM fungi spore populations in those both green houses. Regrowth of sorghum plants (up to ratoon 2) failed to increase the density of AMF spore populations in both ratoon 1 and ratoon 2, and there was even a decrease in AMF spore populations at some incubation days. Drying of media could decrease or increase spore density in propagation in greenhouse H, while agitation to increase aeration couldn't enhance spore populations. In greenhouse I, neither agitation nor drying could increase the number of AMF spores. The highest spore population obtained from greenhouse H with a total propagation period of 49 weeks (12 months 1 week, ratoon 2) was observed at the beginning of maintenance of the second plant (ratoon 1), reaching 8.3 spores g-1, while for greenhouse I with a longer total time of 53 weeks (13 months 1 week, ratoon 2), the highest spore population was at the end of drying in the maintenance of the third plant (ratoon 2), reaching 6.7 spores g-1